Radio Galaxies at TeV Energies - Glawion, Dorit (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
It is common believe that the centers of all galaxies exhibit supermassive black holes with masses ranging from millions up to billions of the mass of our Sun. By accreting surrounding matter, the luminosity of these galactic nuclei can outshine the emission of their host galaxies. If this is the case, they are called active galactic nuclei. Some of these objects eject powerful outflows composed of plasma, called jets. These jets can produce non-thermal radiation which observable across the entire electromagnetic spectrum from radio up to the gamma-ray frequencies. At highest frequencies (TeV range) most of the detected active galaxies have jets directed along or close to the line of sight. However, also galaxies with larger angles to the line of sight showing fascinating features were discovered, in seeming contradiction to traditional models for these so-called radio galaxies. Thus, the latter are of particular importance for understanding active galactic nuclei in general. This Special Issue contains reviews and research articles about the current knowledge of radio galaxies at TeV energies, including observational results and theoretical models. It is intended to guide the interested reader deeper into this fascinating discipline of modern day astronomy.